Food Diversification in Java - Roeskani Sinaga; Manuntun Parulian Hutagaol; Sri Hartoyo; Nunung Nuryartono (GoAcademica Research & Publishing, 2021)
Differences in economic structure, differences in income levels, food price levels cause differences in household consumption patterns. This paper analyzes food diversification in Java. Households are grouped by income group to assess the level of food diversification of each group. Households whose income groups Q3 and Q4 have lower food diversification compared to households in groups Q1 and Q2. The study results show that the value of BI is greater than the value of MBI in both urban and rural areas. This indicates that the source of calories does not come from only one type of commodity. The increase in per capita expenditure does not increase food diversification (the dependent variable is BI) for households in groups Q1 and Q2, while it is positive for households in groups Q3 and Q4. Food prices generally affect diversification. An increase in the number of household members will reduce the level of diversification for Q1 households. In contrast, increasing the number of household members will increase food diversification for Q2, Q3 and Q4 households. The level of household diversification in urban areas is higher than in rural areas.